2021
DOI: 10.3389/fmicb.2021.737116
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-Solubilizing Bacterium Acinetobacter pittii gp-1 Affects Rhizosphere Bacterial Community to Alleviate Soil Phosphorus Limitation for Growth of Soybean (Glycine max)

Abstract: Phosphorus (P) availability is a major restriction to crop production, and phosphate-solubilizing bacteria (PSBs) in soils are responsible for P turnover. However, it remains unknown whether the application of PSB can facilitate both inorganic and organic P transformation and enhance function of plant rhizosphere bacteria. In this study, we applied Illumina MiSeq sequencing, plate-colony counting, quantitative PCR, and multiple ecological analyses. We found that the inoculation of PSB Acinetobacter pittii gp-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 47 publications
(89 reference statements)
0
11
1
Order By: Relevance
“…strain Ac-14 for Arabidopsis thaliana ( 57 ), and Pseudomonas monteilii PsF84 for geranium ( 58 ). The inoculation of PSB can alter community function of soybean rhizosphere bacteria and increase P-cycling-related gene abundance and thus enhance vegetation properties ( 24 ). Previous reports have also reported that inorganic phosphate-solubilizing bacteria can release oxalic, lactic, malic, citric, succinic, and indole-3-acetic acid to enrich soluble P levels ( 9 , 23 , 53 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…strain Ac-14 for Arabidopsis thaliana ( 57 ), and Pseudomonas monteilii PsF84 for geranium ( 58 ). The inoculation of PSB can alter community function of soybean rhizosphere bacteria and increase P-cycling-related gene abundance and thus enhance vegetation properties ( 24 ). Previous reports have also reported that inorganic phosphate-solubilizing bacteria can release oxalic, lactic, malic, citric, succinic, and indole-3-acetic acid to enrich soluble P levels ( 9 , 23 , 53 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the number of PSB using the colony plate counting method ( 24 ). Each soil aggregate (1 g) was added to 10 mL of sterile water.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations